(untitled) (Revista Española de Fisiología, 1991)
The changes in high density lipoprotein (HDL) subfractions have been studied in 106 young healthy men after two months of physical training at a military base. Forty subjects were placed on a heavy intensity training program (HITP) with a daily average energy expenditure estimated as 3,504 Kcal, and 66 subjects followed a moderate intensity training program (MITP) with an average energy expenditure estimated as 2,942 Kcal/day. The HITP group reduced their body fat while HDL-cholesterol, HDL2-cholesterol and apoprotein (apo) A-I increased by 8.4%, 30% and 16.9% respectively (p less than 0.001). Body fat of MITP subjects did not change and HDL-cholesterol, HDL2-cholesterol and apo A-I increased by 5.6% (p less than 0.05), 17.1% (p less than 0.001) and 5.6% (p less than 0.05), respectively. The increase in serum apo A-I level was significantly higher (p less than 0.005) in the heavy intensity training group. The apo A-I/A-II ratio increased significantly in both groups (p less than 0.001), reflecting an increase in the HDL2/HDL3 ratio. This is in agreement with the significant increase in HDL2-cholesterol in both groups (p less than 0.001) with no change or decrease in HDL3-cholesterol.